2022
DOI: 10.1007/s10800-022-01715-9
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lindane using electrokinetic soil flushing coupled with air stripping

Abstract: This paper evaluates the remediation of soil spiked with lindane using a combined treatment consisting of electrokinetic soil flushing (EKSF) with air stripping to elucidate the main processes occurring in the soil when electric fields of 0.75 V cm−1 and 1.50 V cm−1 are applied. The results demonstrate that lindane is efficiently transported to the anodic and cathodic wells using flushing fluids containing sodium dodecyl sulfate (SDS). Additionally, an important amount is volatilized and stripped with the inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…The electric current produced is not proportional to the electric gradient but conversely, it is lower for the higher electric gradient, what initially was unexpected. Similar results were obtained in a previous work of de Melo Henrique et al, [10] which investigated the remediation of soil spiked with lindane using air stripping associated and electrokinetic soil flushing applied different electric fields (0.75 V cm À 1 and 1.50 V cm À 1 ) during 14 days. In this previous work, it was observed that the accumulated charge was higher for the electric field of 0.75 V cm À 1 .…”
Section: Resultssupporting
confidence: 89%
“…The electric current produced is not proportional to the electric gradient but conversely, it is lower for the higher electric gradient, what initially was unexpected. Similar results were obtained in a previous work of de Melo Henrique et al, [10] which investigated the remediation of soil spiked with lindane using air stripping associated and electrokinetic soil flushing applied different electric fields (0.75 V cm À 1 and 1.50 V cm À 1 ) during 14 days. In this previous work, it was observed that the accumulated charge was higher for the electric field of 0.75 V cm À 1 .…”
Section: Resultssupporting
confidence: 89%